A conserved behavioral role for a nematode interneuron neuropeptide receptor. Issue 1 (6th November 2021) - Chai, Cynthia M; Chen, Wen; Wong, Wan-Rong; Park, Heenam; Cohen, Sarah M; Wan, Xuan; Sternberg, Paul W
Abstract: Neuropeptides are evolutionarily conserved modulators of many aspects of animal behavior and physiology, and expand the repertoire of processes that can be controlled by a limited number of neurons. Deciphering the neuropeptidergic codes that govern distinct processes requires systematic functional analyses of neuropeptides and their cognate receptors. Even in well-studied model organisms like Caenorhabditis elegans, however, such efforts have been precluded by a lack of mutant reagents. Here, we generated and screened 21 C. elegans neuropeptide G-protein coupled receptor mutants with no pre-existing reagents for the touch-evoked escape response, and implicated six receptors expressed in diverse neuron classes representing multiple circuit levels in this behavior. We further characterized the mutant with the most severe phenotype, frpr-14, which was defective in multiple behavioral paradigms. We leveraged this range of phenotypes to reveal that FRPR-14 modulation of different precommand interneuron classes, AVH and AIB, can drive distinct behavioral subsets, demonstrating cellular context-dependent roles for FRPR-14 signaling. We then show that Caenorhabditis briggsae CBR-FRPR-14 modulates an AVH-like interneuron pair to regulate the same behaviors as C. elegans but to a smaller extent. Our results also suggest that differences in touch-evoked escape circuit architecture between closely related species results from changes in neuropeptide receptor expression pattern, as opposed to ligand–receptor pairing. This study provides insights into the principles utilized by a compact, multiplexed nervous system to generate intraspecific behavioral complexity and interspecific variation.